THE EFFECT OF FACILITIES AND PROMOTIONS ON REVISIT INTENTION TO MANGGA DUA SQUARE IN NORTH JAKARTA - Adlina Firzana; Fachri Aditya; Imas Chandra Pratiwi; Riza Hadikusuma (UPT Publikasi Ilmiah UNISBA, 2025)
A significant decline in the number of visitors can disrupt the cash flow of the managing company and limit its ability to develop facilities. This study aims to determine the extent to which facilities and promotion influence revisit intention at Mangga Dua Square. The research employed a quantitative method with a PLS-SEM approach using SmartPLS software version 4.1.1.2. Data were collected through questionnaires using purposive sampling, resulting in a sample of 400 respondents. The survey was distributed online via Google Forms. The results show that facilities have a positive and significant effect on revisit intention. This indicates that the better the available facilities, the higher the revisit intention to Mangga Dua Square, North Jakarta. Promotion also has a positive and significant effect on revisit intention. This means that the more precise and consistent the promotional strategy, the more it increases visitors’ intention to return to Mangga Dua Square. Facilities and promotion together have a significant influence on revisit intention, with an f-statistic value of 439.764 and an R-square value of 0.689, meaning that the variables of facilities and promotion can explain 68.9% of revisit intention, while the remaining 31.1% is influenced by other factors not covered in this study.